Maintaining physical activity during head and neck cancer treatment: Results of a pilot controlled trial. (7th October 2015) - Zhao, Shuang G.; Alexander, Neil B.; Djuric, Zora; Zhou, Jessica; Tao, Yebin; Schipper, Matthew; Feng, Felix Y.; Eisbruch, Avraham; Worden, Francis P.; Strath, Scott J.; Jolly, Shruti
Abstract: Background: Concurrent chemoradiotherapy (concurrent CRT) to treat head and neck cancer is associated with significant reductions of weight, mobility, and quality of life (QOL). An intervention focusing on functional exercise may attenuate these losses. Methods: We allocated patients to a 14‐week functional resistance and walking program designed to maintain physical activity during cancer treatment (MPACT group; n = 11), or to usual care (control group; n = 9). Outcomes were assessed at baseline, and 7 and 14 weeks. Results: Compared to controls, the MPACT participants had attenuated decline or improvement in several strength, mobility, physical activity, diet, and QOL endpoints. These trends were statistically significant ( p < .05) in knee strength, mental health, head and neck QOL, and barriers to exercise. Conclusion: In this pilot study of patients with head and neck cancer undergoing concurrent CRT, MPACT training was feasible and maintained or improved function and QOL, thereby providing the basis for larger future interventions with longer follow‐up. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1086–E1096, 2016